Experienced pediatric nurses' perceptions of work-related stressors on general medical and surgical units: A qualitative study. (August 2016) - De Almeida Vicente, Alexandra; Shadvar, Sanaz; Lepage, Stephanie; Rennick, Janet E.
Abstract: Background: Experienced pediatric nurses caring for increasingly sick and vulnerable children on medical and surgical units may be at particular risk for work-related stress. In view of their positive impact on quality of care, and the fact that they are particularly difficult to retain, it is imperative to understand the work-related stressors these nurses encounter in order to develop effective organizational interventions to minimize stressors and promote retention. Objective: To explore experienced pediatric nurses' perceptions of work-related stressors in medical and surgical units. Design: Qualitative descriptive design with semi-structured interviews. Setting: Medical and surgical units at a quaternary care pediatric hospital in Montreal, Canada. Participants: Nurses recognized as experienced by the nursing leadership team as reflected by having been 'in charge' of the unit, or having trained junior staff, and who had been practicing full-time for three years or more on a general medical or surgical pediatric unit were eligible to participate. Purposive sampling was used, and nurses recruited until data saturation was reached ( n  = 12). There were no refusals to participate. Methods: Semi-structured interviews were conducted between August and December 2013. Results: Nurses described a strong sense of responsibility for providing excellent patient care, and identified stressor that negatively impacted their ability to do so. Stressors are reflected in three themes: (1) "The kids are getting sicker and sicker": Difficulty ensuring excellent patient care to an increasingly vulnerable population, (2) Feeling powerless to provide quality care, and (3) Being a "Jack-of-all-trades": Struggling with competing demands. Conclusion: Experienced pediatric nurses felt powerless to provide quality care to an increasingly acute and vulnerable population. Dealing with multiple and diverse responsibilities, and limited resources and support, were important stressors. Nurse Managers and educators could mitigate stressors and improve retention of experienced pediatric nurses by offering targeted continuing education to those newly responsible for additional roles, and building supportive working environments that encourage collaboration and empower experienced nurses.